Evidence‐based medical treatment of POEMS syndrome. (7th August 2022) - Khwaja, Jahanzaib; D'Sa, Shirley; Lunn, Michael P.; Sive, Jonathan
Summary: POEMS syndrome is a rare multisystem paraneoplastic disorder due to an underlying low‐level plasma cell dyscrasia. Due to its rarity, there are limited data to guide treatment and there are no consensus guidelines. Therapy choices are dictated by patient characteristics, disease factors and local funding arrangements. The goals of therapy are to eradicate the underlying clone in order to improve quality of life and overall survival. Most evidence has been garnered in the front‐line setting. Localised disease responds well to radiotherapy, whilst for those with systemic disease, the best outcomes are demonstrated with induction chemotherapy followed up with high‐dose melphalan and stem cell rescue if eligible. For transplant‐ineligible patients lenalidomide–dexamethasone remains a preferred treatment option. Data in the relapse setting are scarce. Supportive care including management of neuropathy, endocrinopathy, thrombotic risk and anti‐infective agents is necessary. Future international collaboration is crucial to define optimal treatment strategies particularly in the relapse setting.